A new species of the sun coral genus Tubastraea (Scleractinia: Dendrophylliidae) from Hong Kong - Yiu, Sam King Fung; Chung, Sheena Suet-Wah; Qiu, Jian-Wen (Zootaxa, 2021)
Tubastraea, commonly known as sun coral, is a genus of brightly coloured azooxanthellate corals in the family Dendrophylliidae. The diversity of this genus is low, with only seven recognized species. Herein, we describe Tubastraea megacorallita sp. nov. from Hong Kong based on morphological and molecular analyses. This new species exhibits several characteristics of the genus including being colonial, having a rough texture of corallum and no epitheca. It can be distinguished from its congenerics by bigger corallites, and the Pourtalès plan arrangement of its septa. The rDNA gene sequences (consisting of ITS1, 5.8S, ITS2, 18S and 28S) showed 2.45–5.18% divergence from those of its closest relatives, T. coccinea and T. micranthus.